Board Interlocks and Initial Public Offering Performance in the United States and the United Kingdom: An Institutional Perspective. (April 2018) - Filatotchev, Igor; Chahine, Salim; Bruton, Garry D.
Building on the institutional perspective on capital markets, we examine the process of legitimation that underpins investor valuation of initial public offerings in the context of institutional polycentricism. We focus on the impact of board interlocks of the CEO and internal and external board members on investor perceptions of initial public offering firms in the United States and United Kingdom. We find that the extent of board members' interlocks relates positively to the extent of the CEO's interlocks, but this relationship is stronger in the United Kingdom than in the United States. More extensive interlocks lead to higher valuations in the United Kingdom than in the United States. This is the result of differences in institutional confluences that underpin corporate governance in the two culturally related countries.